Long-term ice phenology records of Lake Balaton and the Danube River (East Central Europe) - Katalin Takács; Zoltán Kern (PANGAEA, 2017)
A dataset of annual freshwater ice phenology was compiled for the largest river (Danube) and the largest lake (Lake Balaton) in eastern-central Europe, extending regular river and lake ice monitoring data through the use of historical observations and documentary records dating back to AD1774 and AD1885, respectively. What becomes clear is that the dates of the first appearance of ice and freeze-up have shifted, arriving 12-30 and 4-13 days later, respectively, per 100 years. Break-up and ice-off have shifted to earlier dates by 7-13 and 9-27 days/100 years, except on Lake Balaton, where the date of break-up has not changed significantly. The datasets represent a resource for (paleo)climatological research thanks to the strong, physically determined link between water and air temperature and the occurrence of freshwater ice phenomena. The derived centennial records of freshwater cryophenology for the Danube and Balaton are readily available for detailed analysis of the temporal trends, large-scale spatial comparison, or other climatological purposes.
Supplement to: Takács, Katalin; Kern, Zoltán; Pásztor, László (2018): Long-term ice phenology records from eastern-central Europe. Earth System Science Data, 10, 391-404, https://doi.org/10.5194/essd-10-391-2018